ダイ17ジ ナンキョク チイキ カンソク タイ ナツ タイ (1975-1976) ホウコク - 平澤, 威男; ヒラサワ, タケオ; Hirasawa, Takeo (1983)
P(論文) 第17次南極地域観測隊は隊長芳野赳夫以下40名, うち夏隊は平澤威男副隊長以下10名であった。そのほかに, 国立極地研究所永田所長が南極地域視察のため, フランスの交換科学者としてLAURENT氏が, また, オブザーバーとして運輸省船舶技術研究所の竹沢節雄氏が同行した。1975年12月16日フリマントル出港, 30日氷縁に達し, 1976年1月3日早朝, 昭和基地の北方53海里の地点から第1便を基地へ送った。その後本格空輸が開始され, 2月18日に終了した。その間, 輸送と並行して, 基地建設が行われ, 主としてロケット基地再開に伴う施設整備作業が実施された。2月1日予定通り第17次越冬隊が成立した。船上の観測はおおむね例年通りであったが, 氷海域において, グラビティコアラーによる柱状採泥があらたに行われた。沿岸域においては, 氷河地形, 寒冷生物の生態系の調査, および基準点測量が実施された。また国際磁気圏観測計画(IMS)の第1年度として, 夏期にS-210JAとS-310JA型ロケットの打ち上げが行われ, 実験に成功した。 Summer operation of the 17th Japanese Antarctic Research Expedition (JARE-17) is outlined. The expedition led by T. YOSHINO consisted of 40 members, 10 of which are of the summer party led by T. HIRASAWA, deputy leader of the expedition. After leaving Fremantle in Australia, the icebreaker FUJI reached a site 53 nautical miles north of Syowa Station on January 3,1976. All of the cargo for the 17th expedition was transported to Syowa Station until February 18,1976,while the construction work was carried out at Syowa Station. On February 1,1976,the wintering members of JARE-17 took over the duties at the station. Oceanographic and biological observations were carried out throughout the voyage, and also marine geographical studies were conducted within the sea ice area. Several field parties for geographical, biological and geodetic surveys were sent to exposed rocks around Syowa Station. A round trip to the inland Mizuho Station (formally Mizuho Camp, officially redesignated in March 1978) was carried out to deliver the cargo. Two rockets for the studies of upper atmosphere physics were launched at Syowa Station during the summer season. departmental bulletin paper